The Use of Smartphones as an Educational Tool in the Classroom: Lecturers’ Perceptions - Wali, Ahmad Zahir; Omaid, Mohammad Ehsan (International Journal of Emerging Technologies in Learning (iJET), 2020)
This paper aims to study the lecturers’ perceptions toward the use of smartphone as an educational tool in classroom. The study also investigates the benefits and perceived barriers of smartphone use by students in classroom from the lecturers’ perspective. A quantitative research design was employed and data from a random sample of 50 lecturers of Kandahar University was collected using a questionnaire. The data was analysed by descriptive statistics using SPSS v24 software. The findings revealed that the lecturers allow the use of smartphone as an educational tool in classroom for all its functions except for the use of social media. The findings also indicated that the lecturers perceive the use of smartphone by the students in classrooms to be beneficial for students in their learning in various ways. Moreover, the findings showed no major perceived barriers by the lecturers’ for the students’ use of smartphones in classroom.